Management discriminant properties in semiarid soils (Semiárida, 2020)
The physical properties of coarse - textured soils in semiarid regions often deteriorate with use. We hypostatized that the changes in the physical properties of the soil were related to the cropping sistem employed. 5urface sampled of 52 Entic Haplustolls under three diferents uses (24 under continuous cultivation), 18 under rotation wuth grass Ieys (R), and 10 virgin soils M were analyzed for c1ay, silt, organic malter anrd water content, bulk density, compaction and aggregate stability. Data were analyzed statistically using principal components, canonical variables, and discriminant functions. A satisfactory segregation of the soils according to discriminant properties (coarse organic matter, aggregate stability, and suceptibility lo compaction) was obtained. The model developed satisfactory classified the soils under different uses (100% R, 83% e, and 88% V). Principal component analysis also showed that bulck density, compaction, and wet aggregate salability are related lo organic matter content. We conclude that, in the studied region, the lower the ratio of organic matter lo clay + soil content, the more severe the physical deterioration of the soils.Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.)Publicado en Soil Science, Vol 163 N°7.